IMPACT OF BALL BEARING DAMAGE VARIATIONS ON THE EFFICIENCY OF SQUIRREL CAGE 3-PHASE INDUCTION MOTORS - Widagdo, Reza Sarwo; Andriawan, Aris Heri; Prenata, Giovanni Dimas (-, 2024)
This research aims to determine the initial diagnosis of damage to a 3-phase induction motor. Ball bearings are one of the important components in this induction motor which play a role in supporting the load and allowing smooth rotation. However, like all mechanical components, ball bearings in 3-phase induction motors are also susceptible to failure in motor performance and can even cause damage to the motor as a whole. There are ways to detect several disturbances in induction motors, namely through speed analysis, current fluctuations, and increases in motor temperature when operating. Based on the results of measurement data for 14 days, the average current value in normal bearing conditions is 1.36 A, while in broken bearing conditions the average current value is 1.55 A and in rusty bearing conditions 1.52 A. The increase in current is due to because the rotor does not rotate in a balanced manner so that the electric field in the stator changes, this causes an increase in the motor's current and temperature.